Tumor-dependent myeloid and lymphoid cell recruitment in genO-BRGSF-HIS mice: a novel tool for evaluating immunotherapies - Martin, Gaëlle H.; Hedir, Siham; Creusat, Florent; Gonon, Alexis; Marguier, Amélie; Martin-Jeantet, Perrine; Nouveau, Lise; Cons, Laura; Renart-Depontieu, Florence; Moine, Valery; Derive, Marc; Cherifi, Yacine; et al. (Frontiers in Immunology, 2025)
ObjectivesPreclinical models that accurately recapitulate the human immune response, particularly within the tumor microenvironment (TME), are needed for the translational and predictive testing of new therapies. Here, we examine whether the genO-BRGSF-HIS model—characterized by robust reconstitution of both human lymphoid and myeloid cells following engraftment with CD34+ cord blood cells—could be a translatable mouse model for human tumor biology and a relevant platform for evaluating novel immunotherapies.MethodsgenO-BRGSF mice were reconstituted with human CD34+ cord blood cells (genO-BRGSF-HIS) and treated with exogenous human Flt3 ligand (hFlt3L). Myeloid and dendritic cell functionality was analyzed following treatment with different compounds (TLR agonists, TREM1 agonist, STING agonist, or T-cell engagers) and following the implantation of different tumor cell lines (MDA-MB-231, A549, HPAF-II).ResultsWe show that myeloid, dendritic and lymphoid cells (including NK and γδ T cells) are functional and recruited into the TME in genO-BRGSF-HIS mice implanted with different tumor cell lines, and that different immune cell populations are activated and get polarized within the TME. The composition of the TME is dependent on tumor type and tumor burden, demonstrating plasticity in the crosstalk between the human immune system and the tumor cells. Furthermore, we observed polarization of the cells recruited to the TME, as well as a wide diversity of recruited cell populations, suggesting that this model reproduces human physiopathology in the context of cancer. Based on the recruitment of the different cell populations according to tumor type, we also demonstrate that this model can be used for testing new therapies targeting lymphoid cells, such as T-cell engagers.ConclusionsgenO-BRGSF-HIS mice do not exhibit adverse effects associated with the development of human lymphoid and myeloid cells following CD34+ cord blood cell reconstitution, and their extended lifespan allows for longer experimental study windows. Overall, we show that this model develops functional myeloid and lymphoid cells which are recruited to the TME, making it a valuable tool for testing new immunotherapies that modulate the interaction between the tumor and the immune system.